2005
DOI: 10.1093/nar/gki433
|View full text |Cite
|
Sign up to set email alerts
|

GraBCas: a bioinformatics tool for score-based prediction of Caspase- and Granzyme B-cleavage sites in protein sequences

Abstract: Caspases and granzyme B are proteases that share the primary specificity to cleave at the carboxyl terminal of aspartate residues in their substrates. Both, caspases and granzyme B are enzymes that are involved in fundamental cellular processes and play a central role in apoptotic cell death. Although various targets are described, many substrates still await identification and many cleavage sites of known substrates are not identified or experimentally verified. A more comprehensive knowledge of caspase and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 15 publications
0
99
0
Order By: Relevance
“…Current efforts at predicting caspase cleavage sites in proteins are focused on prediction through searching for potential sites in translated genomic data using inherent substrate specificity models. [38][39][40] Others have developed caspase prediction software and neural network analysis that uses examples of known cleavage sites (training sets) to infer preferred cleavage site amino acids, 41,42 but here the major question must be the quality of the training set ( Table 1). The uncontrolled variable is the quality of the data used to define the training set, which is often based simply on literature reports.…”
Section: What It Takes To Be a Caspasementioning
confidence: 99%
“…Current efforts at predicting caspase cleavage sites in proteins are focused on prediction through searching for potential sites in translated genomic data using inherent substrate specificity models. [38][39][40] Others have developed caspase prediction software and neural network analysis that uses examples of known cleavage sites (training sets) to infer preferred cleavage site amino acids, 41,42 but here the major question must be the quality of the training set ( Table 1). The uncontrolled variable is the quality of the data used to define the training set, which is often based simply on literature reports.…”
Section: What It Takes To Be a Caspasementioning
confidence: 99%
“…The results showed that a sufficient amount of the 16-kDa fragment would accumulate in a 3-h treatment for sequence analysis. Protein bands representing Hax-1 fragments were excised from an electroblotted membrane and subjected to Edman degradation and bioinformatic analysis (49). The major cleavage site for GrB was Asp 148 (D148 in Fig.…”
Section: Mapping Of Hax-1 Cleavage Sites-mentioning
confidence: 99%
“…Absence of DNA was evaluated by AluPCR with A1S primer (5Ј tca tgt cga cgc gag act cca tct caa a 3Ј). Reverse transcription was performed by using oligo(dT) [12][13][14][15][16][17][18] primers (Invitrogen) and Omniscript RT Kit (Qiagen). Primer sequences used for PCR were as follows: GAPDH for (5Јggaaggt-gaaggtcggagt3Ј), GAPDH reverse (5Јatcacgccacagtttccc3Ј), SOX2 EST forward (5Јcctccgggacatgatcag3Ј), SOX2 EST reverse (5Јttctc-ccccctccagttc3Ј), SOX2 genomforward (5Јagtctgccgagaatccatgt3Ј), SOX2 genomreverse (5Јtgctttcttggctgagcac3Ј), NKTR RT forward (5Јagctactctagaagtcggagc3Ј), NKTR RT reverse (5Јcgattataacttct-gcctcgg3Ј), KIAA1344 RT forward (5Јtgattttgttcagtgatggcactg3Ј), and KIAA1344 RT reverse (5Јgatatgattttctagtcctgcttc3Ј).…”
Section: Immunoscreening Of Recombinant Proteins (Standard Serex)mentioning
confidence: 99%
“…de) for information on domains. Prediction of cleavage sites for granzyme B was done by GRABCAS, a recently developed prediction tool for granzyme B and caspase cleavage sites (16) that is based on experimentally determined substrate specificities (17).…”
Section: Immunoscreening Of Recombinant Proteins (Standard Serex)mentioning
confidence: 99%